Correlation of doppler studies at 34 weeks of gestation with perinatal outcome in high risk pregnancies - Reddy, Apoorva; Malik, Renuka; Mehra, Shibani; Singh, Pushpa; Ramachandran, Lakshman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Antepartum detection of the fetus at risk of death or compromise in utero remains a major challenge in modern obstetrics. The waveform analysis of the feto- maternal circulation by Doppler ultrasound has therefore become a quick and a simple way of screening and identifying fetal compromise. The main objective of the study is to evaluate Doppler flow indices as an index for assessing fetal well being in high risk pregnancies and to determine the predictive value of various Doppler parameters with perinatal outcome. Methods: The study was a prospective cohort study were forty pregnant women with a high risk factor (intrauterine growth restriction, pre eclampsia and gestational diabetes mellitus) and forty pregnant women with no high risk(controls) were selected at 34 weeks of gestation. Both the groups underwent an obstetrical ultrasound with color Doppler examination of bilateral uterine arteries, umbilical artery and middle cerebral artery. Abnormality was serially monitored and pregnancy terminated in the presence of absent, reversal of end diastolic flow in umbilical artery or non-reassuring tests of fetal wellbeing. Results: Uterine artery S/D abnormality was seen in 32.5% of high risk cases were as abnormal umbilical artery S/D was seen in 25% and abnormal Pulsatility Index (PI) in 15% cases. Middle cerebral artery flow was abnormal in only 17.5% cases. Abnormality in the uterine artery flow correlated well with the incidence of preterm delivery (69.2%), need for cesarean section (53.8%) and length of Neonatal intensive care unit(NICU) stay >48 hours (69.23%). Abnormal umbilical artery flow was associated with a significant increase in the incidence of preterm delivery(75%), small for gestational age babies(93.75%) and length of NICU stay >48 hours (93.75%). There was no significant correlation seen with isolated abnormal middle cerebral artery flow. Conclusions: Both uterine and umbilical artery Doppler velocities correlate well with the perinatal outcome but abnormal uterine artery Doppler predicts adverse neonatal outcome better than the fetal vessels as it discriminates fetuses at risk because of abnormal placental vascularisation from those who are at risk due to other causes.